Ardaxšīr and the Sasanians’ Rise to Power - Daryaee, Touraj (Anabasis. Studia Classica et Orientalia, 2010)
The author deals with the rise to power of Ardaxšīr ī Pābagān and his family origins. The sources are either late (Perso-Arabic), or foreign and hostile (Greek and Armenian), or concerned with external religious matters (Syriac) which tend to be helpful mainly for chronology. Material culture, specifically coinage along with the rock reliefs are of the utmost importance to this investigation, and it is these sources that need to be juxtaposed with the literary documents to achieve a more balanced view of the origins of the Sasanians.